Does Eumelanin Oxidation Play a Role on the Photostability of Ethyl Glucuronide in Hair Exposed to Simulated Solar Radiation?. Issue 7 (17th October 2020) - Miolo, Giorgia; Vicario, Benedetta; Stocchero, Giulia; Causin, Valerio; Vogliardi, Susanna; Favretto, Donata
Abstract: The action of solar radiation on the concentration of the ethanol metabolite ethyl glucuronide (EtG) in 40 hair samples of nonabstinent subjects was investigated. Hair samples of different colors were analyzed before and after irradiation with artificial sunlight under a light dose corresponding to 3 months of sun exposure. After irradiation, an increase of EtG concentration was detected in 55% of the samples ranging from 5% to 141%. In 16 cases, a concentration reduction ranging from −2% to −74% was observed. The measure of the level of pyrrole-2, 3, 5-tricarboxylic acid (PTCA), a marker of eumelanin oxidation, demonstrated the largest increase in oxidation in light brown hair where the greatest degradation of EtG was observed after irradiation. However, the rise of PTCA in all hair tested was accompanied by increase in EtG concentration in 8/10 samples and by decrease in 2/10, suggesting no correlation between the two markers. To verify if hair structure was modified by light, scanning electron microscopy (SEM) analysis was performed on irradiated hair of different colors and compared with the dark samples. SEM revealed modification of hair structure in all samples showing partial shaft exfoliation and reduction of hair thickness under the treatment with solar radiation.